Generation of broad-band circularly polarised supercontinuum in chiral photonic crystal fibre - Sopalla, R.; Wong, G. K.L.; Joly, Nicolas; Jiang, X.; Frosz, M. H.; Ahmed, G.; Russell, Philip St. John (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Supercontinuum (SC) generation in solid-core photonic crystal fibres (PCFs) is well established and has diverse applications in science and technology [1,2]. In a conventional SC, the polarization state is not maintained over the whole spectrum due to cross-phase modulation and may in addition vary with power. Recently, it has been reported that continuously twisted PCFs exhibit circular birefringence [3,4]. Here we report the first experimental demonstration of a twisted PCF that robustly maintains circular polarization state across the whole spectrum, independent of power.
CRIS-Team Scopus Importer:2019-11-15